Cis -2,2′-bipyrimidine-bridged polynuclear complex: A stairway-like mixed-valent Fe4 cluster - Alborés, Pablo (2010)
We report the first example of a polynuclear discrete coordination compound exhibiting only bpym bridges and containing a first-row d transition metal. A smooth self-assembly one-pot synthetic route, starting from simply FeCl 2 and FeCl3 hydrates, allowed us to prepare a tetranuclear Fe4 cluster with a stairway-like structure and the formula cis-{[(H2O)Cl3FeIII-μ(bpym)Fe IICl2]}2-μ(bpym) (1). All spectroscopic data suggest that complex 1 is a valence-localized mixed-valent Fe II-FeIII cluster with typical Mössbauer lines for both sites, which do not change with temperature. Reflectance spectroscopy did not allow one to distinguish an intervalence charge-transfer band. However, time-dependent density functional theory (DFT) calculations predict a weak high-energy FeII → FeIII transition. Regarding the magnetic properties, the high-spin FeII and FeIII ions interact in a weakly antiferromagnetic way with isotropic J constants of only a few wavenumbers as derived from direct-current susceptibility and magnetization data. Broken-symmetry DFT calculations support these observations. © 2010 American Chemical Society.